2014
DOI: 10.1016/j.tet.2014.05.102
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bis(1′-ortho-carboranyl)benzenes and bis(1′-ortho-carboranyl)biphenyls

Abstract: . (2014) 'Studies on bis(1'-ortho-carboranyl)benzenes and bis(1'-ortho-carboranyl)biphenyls. ', Tetrahedron., 70 (34). pp. 5182-5189.Further information on publisher's website:http://dx.doi.org/10.1016/j.tet.2014.05.102Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Tetrahedron. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Ishigaki, Suzuki, and co‐workers obtained a series of dispiro(acridan)‐substituted pyracene and acenaphthenes with C−C bond lengths of up to 180.6 pm . Also for closo ‐1,2‐dicarbadodecaboranes, with formally hexa‐coordinated carbon atoms and a multicenter bonding situation, many experimental results reveal C−C bonds that are longer than 174.8 pm . Previous density‐functional theory (DFT) computations indicated that 1,2‐(NH 2 ) 2 ‐ o ‐carboranes could have strikingly long C−C bonds .…”
Section: Figurementioning
confidence: 99%
“…Ishigaki, Suzuki, and co‐workers obtained a series of dispiro(acridan)‐substituted pyracene and acenaphthenes with C−C bond lengths of up to 180.6 pm . Also for closo ‐1,2‐dicarbadodecaboranes, with formally hexa‐coordinated carbon atoms and a multicenter bonding situation, many experimental results reveal C−C bonds that are longer than 174.8 pm . Previous density‐functional theory (DFT) computations indicated that 1,2‐(NH 2 ) 2 ‐ o ‐carboranes could have strikingly long C−C bonds .…”
Section: Figurementioning
confidence: 99%
“…Structured bands and higher coefficients (ε = 310-420 L mol -1 cm -1 ) were observed in 7 and 8 where π→π* transitions in the phenyl group present are responsible for these bands. [49,50] The absorption spectra for 9 or 10 showed one unstructured band slope tailing off at ca. 300 nm.…”
Section: Absorptionmentioning
confidence: 99%
“…Electronic communication between the carborane cages via the para-phenylene bridge is found only in the para-substituted benzene compound. 14 CuCl-mediated C-C coupling of dilithiocarborane in toluene is a facile and practical method for the preparation of 1,1 0 -bis(o-carborane) (Scheme 5). The reaction intermediate 1,1 0 :2,2 0 -[Cu(toluene)] 2 (C 2 B 10 H 10 ) 2 is isolated from the reaction system before hydrolysis, which confirms the transmetalation process.…”
Section: Copper-mediated Reaction Of Lithiocarboranementioning
confidence: 99%